Musculoskeletal multibody dynamics simulation of the contact mechanics and kinematics of a natural knee joint during a walking cycle. (May 2018) - Hu, Jiayu; Chen, Zhenxian; Xin, Hua; Zhang, Qida; Jin, Zhongmin
Detailed knowledge of the in vivo loading and kinematics in the knee joint is essential to understand its normal functions and the aetiology of osteoarthritis. Computer models provide a viable non-invasive solution for estimating joint loading and kinematics during different physiological activities. However, the joint loading and kinematics of the tibiofemoral and patellofemoral joints during a gait cycle were not typically investigated concurrently in previous computational simulations. In this study, a natural knee architecture was incorporated into a lower extremity musculoskeletal multibody dynamics model based on a force-dependent kinematics approach to investigate the contact mechanics and kinematics of a natural knee joint during a walking cycle. Specifically, the contact forces between the femoral/tibial articular cartilages and menisci and between the femoral and tibial/patellar articular cartilages were quantified. The contact forces and kinematics of the tibiofemoral and patellofemoral joints and the muscle activations and ligament forces were predicted simultaneously with a reasonable level of accuracy. The developed musculoskeletal multibody dynamics model with a natural knee architecture can serve as a potential platform for assisting clinical decision-making and postoperative rehabilitation planning.